Green environment-friendly heat-resistant photovoltaic cable and preparation method thereof
The composite material of porous PET and rigid PVC was prepared by suspension polymerization and emulsion method, which solved the problem of poor compatibility between polyethylene terephthalate and polyvinyl chloride, and realized an environmentally friendly and heat-resistant photovoltaic cable sheath layer material.
Patent Information
- Application Number
- CN202510279140.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-11
AI Technical Summary
The prior art is difficult to improve the compatibility between polyethylene terephthalate and polyvinyl chloride, resulting in poor performance of its composite sheathing materials in terms of heat resistance and environmental protection.
Hard PVC is prepared by suspension polymerization method, and PVC paste resin is prepared by emulsion method to modify the porous PET to improve its compatibility with hard PVC, thereby preparing environmentally friendly and heat-resistant photovoltaic cable sheath layer material.
The good compatibility between polyvinyl chloride and polyethylene terephthalate composite material is achieved, and the mechanical properties, flame retardant properties and dimensional stability of the sheath layer are improved, so that it can show good heat resistance and green environmental protection characteristics under high temperature environments.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cable processing, and in particular to a green, environment-friendly, heat-resistant photovoltaic cable and a preparation method thereof. Background Art
[0002] Photovoltaic cables are special cables in solar power generation systems, mainly used for power transmission between components and between components and inverters. The basic structure of photovoltaic cables includes: conductor core, insulation layer and sheath layer. The conductor is usually made of high-purity oxygen-free copper or tinned copper, the insulation layer is usually made of polymer, and the sheath layer is made of polymer or composite material.
[0003] The function of the sheath layer is to protect the cable core and prevent the cable core from being damaged by stretching, bending or extrusion during installation or use. In recent years, for the sake of green environmental protection, biodegradable polymer materials such as polylactic acid (PLA), polybutylene succinate (PBS), polyhydroxyalkanoate (PHA), polyethylene terephthalate (PET) have gradually been used in cable sheath layers.
[0004] For example, the Chinese patent application with publication number CN114729176A discloses a cable insulation material for automobiles with polyethylene terephthalate as the main raw material. The Chinese patent application with publication number CN105348575A discloses a cable sheath rubber with natural rubber and polylactic acid as the main raw materials. The Chinese patent application with publication number CN117766215A discloses a cable sheath with a block copolymer composed of polylactic acid, terephthalic acid (PTA) and polyethylene glycol (PEG) as the main raw material.
[0005] Considering the problems of weather resistance, cost, mechanical strength, etc., it is not realistic to use degradable materials to manufacture cable sheaths. Therefore, mixing traditional polymers and degradable polymer materials to prepare cable sheath layers has become a development trend in this field.
[0006] For example, existing technologies including Chinese patent applications such as CN104861352A and CN107090147A have attempted to prepare cable materials by mixing polyvinyl chloride (PVC) and polyethylene terephthalate and adding other additives.
[0007] Polyvinyl chloride materials have been widely used in the preparation of sheath layers, and polyethylene terephthalate can improve the degradability and heat resistance of polyvinyl chloride materials. However, in terms of chemical structure, polyethylene terephthalate is a thermoplastic polyester, while polyvinyl chloride is a polar plastic. The molecular chain structure and polarity of these two plastics are different, resulting in a lack of sufficient interaction between them, making it difficult to form good compatibility. Therefore, how to improve the compatibility between polyethylene terephthalate and polyvinyl chloride has always been a technical problem to be solved by technical personnel in the field, and is also the key to successfully obtaining a polyvinyl chloride and polyethylene terephthalate composite sheath material that is both environmentally friendly and heat-resistant. Summary of the invention
[0008] One of the problems solved by the present invention is how to provide an environmentally friendly and heat-resistant photovoltaic cable with polyvinyl chloride and polyethylene terephthalate as a composite sheath layer.
[0009] In order to solve at least one of the above problems, the present invention provides a method for preparing a green, environmentally friendly, heat-resistant photovoltaic cable, comprising: S1, preparing a first PVC by suspension polymerization; S2, preparing a second PVC by an emulsion method; S3, using the second PVC to modify the porous PET to obtain modified PET; S4. Melt-extrude the raw materials including the first PVC and the modified PET, and coat the surface of the cable core as a sheath layer to obtain a photovoltaic cable.
[0010] In any of the above technical solutions, the first PVC is hard PVC, and the second PVC is PVC paste resin.
[0011] In any of the above technical solutions, the porous PET is prepared by the following steps: A1. Using acetylated chitosan as a porogen and inorganic non-metallic oxide as a flame retardant, adding acetic acid and water and mixing evenly to prepare a suspended first aqueous phase; A2, using PET and organic solvent to prepare the first oil phase; A3, obtaining a first emulsion by mixing and emulsifying the first water phase and the first oil phase; A4. Add polyvinyl alcohol to the first emulsion, heat and stir evenly, let it stand, and then distill under reduced pressure to remove the solvent to obtain porous PET.
[0012] In any of the above technical solutions, in step S2, the raw materials used include glutamic acid.
[0013] In any of the above technical solutions, in step A1, the mass ratio of acetylated chitosan: inorganic non-metallic oxide: acetic acid: water is (1-2): (2-4): (4-8): 100.
[0014] In any of the above technical solutions, in step A2, the mass ratio of PET: organic solvent is (6-12):100.
[0015] In any of the above technical solutions, in step A2, the organic solvent includes phenol and tetrachloroethane in a mass ratio of 1:1.
[0016] In any of the above technical solutions, in step A2, the first oil phase is prepared by heating PET and an organic solvent to 65° C. to 75° C., keeping warm, and magnetically stirring at a speed of 400 rpm / min to 500 rpm / min until PET is completely dissolved.
[0017] In any of the above technical solutions, in step A3, the mass ratio of the first water phase: the first oil phase = (80-120):100.
[0018] In any of the above technical solutions, in step A3, the mixing and emulsification method is: the first water phase is added dropwise into the first oil phase at 65°C to 75°C and stirred, and after the addition is completed, the mixture is kept warm and ultrasonically emulsified at a power of 400W to 600W and a frequency of 60kHz to 80kHz for 20min to 40min.
[0019] In any of the above technical solutions, in step A4, the mass ratio of the first emulsion to polyvinyl alcohol is 100:(6-12).
[0020] In any of the above technical solutions, in step A4, the method of heating and stirring uniformly is: magnetically stirring at a temperature of 95° C. to 98° C. and a rotation speed of 100 rpm / min to 200 rpm / min until the polyvinyl alcohol is completely dissolved.
[0021] In any of the above technical solutions, in step A4, natural cooling is carried out during the standing process, and the standing time is 20 minutes to 40 minutes.
[0022] In any of the above technical solutions, in step A4, after the reduced pressure distillation, the solid matter is extracted, washed and dried to obtain the porous PET.
[0023] In any of the above technical solutions, step S1 specifically includes: S11, dissolving and uniformly dispersing the dispersant in water at a mass ratio of dispersant: first initiator: water = (0.2-1): (1-3): 100, adjusting the pH value to 7 to 9, adding the first initiator dissolved in an organic solvent, and feeding into a polymerization kettle; S12, adding the first vinyl chloride monomer to the polymerization kettle at a mass ratio of the first vinyl chloride monomer: water = (200-300): 100 and according to the amount of water added in S11, to form a suspension with water; S13, in an inert gas atmosphere, heating the sealed polymerization kettle to 55° C. to 65° C. to carry out a polymerization reaction and detecting the pressure in the polymerization kettle; S14. When the real-time pressure in the polymerization kettle drops to 25% to 30% of the peak pressure in the polymerization kettle, the polymerization reaction is terminated, the temperature is lowered and the pressure is released, the solids are separated, washed and dried, and the first PVC is obtained.
[0024] In any of the above technical solutions, step S2 specifically includes: S21, dissolving glutamic acid in water at a mass ratio of glutamic acid: water = (4-6): 100 to prepare a second aqueous phase; S22, according to the mass ratio of stabilizer: second initiator: plasticizer: emulsifier: second vinyl chloride monomer = (8-12): (1-2): (1-2): (2-8): 100, the stabilizer, the second initiator, the plasticizer, the emulsifier and the second vinyl chloride monomer are uniformly mixed to prepare a second oil phase; S23, adding the second aqueous phase dropwise into the second oil phase at a mass ratio of second aqueous phase: second oil phase = (100-150): 100 and emulsifying to obtain a second emulsion; S24, adding polyvinyl alcohol and water to the second emulsion, heating and stirring to react and standing, centrifuging and separating the product, washing, and obtaining a second PVC.
[0025] In any of the above technical solutions, step S3 specifically includes: S31, mixing the second PVC in tetrahydrofuran in a mass ratio of second PVC: porous PET: water: tetrahydrofuran = (4-6): (20-25): (8-12): 100, adding the mixture of porous PET and water, adjusting the pH value to 7 to 8, and performing ultrasonic treatment; S32. After the ultrasonic treatment is completed, tetrahydrofuran and water are removed by rotary evaporation to obtain modified PET.
[0026] In any of the above technical solutions, step S4 specifically includes: S41, laying out the cable core and preheating it; S42. According to the mass ratio of auxiliary agent: modified PET: first PVC = (4-8): (10-15): 100, the raw materials including auxiliary agent, modified PET and first PVC are melt-extruded at a temperature of 180°C to 200°C, coated on the surface of the cable core, and then wound up after cooling to obtain a photovoltaic cable.
[0027] The present invention also provides a green, environmentally friendly, heat-resistant photovoltaic cable, which is obtained by using a preparation method according to any of the above technical solutions.
[0028] Beneficial Effects The present invention provides a method for preparing a green, environmentally friendly, heat-resistant photovoltaic cable. The method first prepares a first PVC by a suspension polymerization method, and prepares a second PVC by an emulsion method. Then, the second PVC is used to modify porous PET to obtain modified PET. Finally, the raw materials including the first PVC and the modified PET are melt-extruded and coated on the surface of the cable core as a sheath layer to obtain a photovoltaic cable.
[0029] On the one hand, the advantages of polyvinyl chloride are good electrical insulation, corrosion resistance, anti-aging, and flame retardant properties. Polyethylene terephthalate has better degradability and bio-friendliness. Therefore, by adding polyethylene terephthalate, the degradability of polyvinyl chloride materials can be improved, the degradation rate can be increased, the degradation difficulty can be reduced, and it is more environmentally friendly. In addition, polyethylene terephthalate has good crystallinity. Adding it to polyvinyl chloride can reduce the thermal shrinkage of the material and improve the cable's good dimensional stability under high-temperature use environments. Finally, adding polyethylene terephthalate to polyvinyl chloride can enhance the mechanical properties of the cable material, especially tensile strength and toughness, thereby making the cable more resistant to stretching and having a greater elongation at break. Therefore, by compounding polyvinyl chloride with polyethylene terephthalate, a sheath layer material with optimized environmental performance and heat resistance can be obtained, which is not only easier to degrade, but also can maintain dimensional stability in the natural environment of hot summer, and is not easy to deform and damage.
[0030] In the second aspect, considering the poor compatibility between polyethylene terephthalate and polyvinyl chloride, the present invention improves the compatibility between polyethylene terephthalate and polyvinyl chloride through the following process. First, the present invention treats polyethylene terephthalate to form a porous state, that is, porous PET. Secondly, the present invention uses the PVC paste resin (i.e., the second PVC) prepared by the emulsion method to modify the porous PET. The pore structure makes the porous PET have a larger specific surface area and better adsorption performance. The PVC paste resin prepared by the emulsion method of the present invention has a smaller particle size and better flowability. The porous PET is treated with it, so that the small-particle PVC is more easily attached to the surface of the porous PET. The present invention uses the hard PVC (i.e., the first PVC) prepared by the suspension polymerization method, which is used as the main material of the sheath layer. The compatibility between the porous PET modified by the second PVC and the first PVC is improved and improved, so a sheath layer material with uniform and stable properties, better performance and longer service life can be prepared.
[0031] In the third aspect, the present invention uses a water-oil mixed emulsification method to prepare an emulsion in some key processes, and uses the hydrophilicity of polyvinyl alcohol to extract the water phase in the emulsion. Thus, the present invention can add a modifying substance to the water phase, prepare the modified substance into an oil phase, and extract the water phase by polyvinyl alcohol, so that the modifying substance can modify the modified substance. Specifically, in order to prepare porous PET, the present invention dissolves PET in an organic solvent to form an oil phase, and dissolves chitosan in water under the action of acetic acid, and forms an oil-in-water emulsion by mixing and emulsifying water and oil. In the process of adding polyvinyl alcohol to the emulsion and heating and stirring, the polyvinyl alcohol gradually dissolves, and the water phase carrying chitosan wrapped by the oil phase in the emulsion moves outward from the inner core through the oil phase to form a pore in PET, thereby forming a porous PET with uniform pore distribution. In the process of preparing the second PVC by the emulsion method, vinyl chloride monomer is prepared as an oil phase, and glutamic acid is prepared as an aqueous phase, and an oil-in-water emulsion is formed by mixing and emulsifying water and oil. In the process of adding polyvinyl alcohol to the emulsion and diluting it with water, glutamic acid follows the water phase and moves outward from the inner core through the oil phase, and the polymerization reaction is driven by heating to obtain a second PVC modified by glutamic acid. The porous PET contains a small amount of chitosan that exhibits cationic properties when it comes into contact with water, and when glutamic acid comes into contact with water, its carboxyl group dissociates hydrogen ions in a neutral or weakly alkaline environment, so it has anionic properties. Therefore, in the process of using the second PVC obtained from S21 to S23 in S31 to treat the porous PET obtained from A1 to A4, the electrostatic adsorption of anions and cations helps the porous PET to uniformly adsorb the second PVC, further improving the compatibility between the modified PET and the first PVC during the melt extrusion process.
[0032] Fourthly, although the small amount of chitosan remaining in the porous PET can be decomposed during the melting process at nearly 200°C, considering that ordinary chitosan with hydroxyl groups will be dehydrated during the melting process. Polyethylene terephthalate materials are easily degraded when exposed to water under high temperature conditions, resulting in reduced mechanical properties of the sheath layer. In order to avoid the above situation, the present invention uses acetylated chitosan, by replacing the hydroxyl groups in the chitosan molecules with acetyl groups, to avoid the degradation of polyethylene terephthalate materials under high temperature melting conditions and improve the mechanical properties of the sheath layer.
[0033] Fifthly, the flame retardant property of polyethylene terephthalate is weaker than that of polyvinyl chloride, which means that in extreme cases such as fire, polyvinyl chloride materials containing polyethylene terephthalate are more likely to burn and spread than pure polyvinyl chloride materials. For this reason, in the process of modifying porous PET, the present invention adds inorganic non-metallic oxides as flame retardants to the water phase. By preparing the water phase with the flame retardant and chitosan together, the flame retardant can be evenly mixed in the PET material under the extraction effect of the water phase of polyvinyl alcohol, and attached to the pores inside and on the surface of the porous PET, thereby improving the flame retardant property of the sheath layer. DETAILED DESCRIPTION
[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, a detailed description is given below in conjunction with specific embodiments of the present invention.
[0035] Unless otherwise specified, the reagents and raw materials used in the present invention can be purchased through commercial channels. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications.
[0036] The present invention provides a method for preparing a green, environmentally friendly, heat-resistant photovoltaic cable, which at least includes a cable core and a sheath layer. The core structure of the cable core is a conductor, and the outer periphery of the conductor is wrapped with an insulating layer. A conductor shielding layer can be arranged between the conductor and the insulating layer. The outer periphery of the insulating layer can also be wrapped with an insulating shielding layer. In addition, a water-blocking tape layer can also be arranged outside the insulating shielding layer. The conductor is generally twisted with high-purity oxygen-free copper or tinned copper, and the insulating layer is generally prepared from polymer compounds such as polyvinyl chloride, polyethylene, ethylene-propylene rubber, or a combination thereof. The conductor shielding layer and the insulating shielding layer are used to smooth the electric field distribution, prevent local discharge and electromagnetic interference, and generally can be made of metal materials or semiconductor materials. The water-blocking tape layer is usually made of highly absorbent fibers or non-woven fabrics impregnated with highly absorbent resins.
[0037] The present invention uses polyvinyl chloride (hereinafter referred to as PVC) and polyethylene terephthalate (hereinafter referred to as PET) as main raw materials for the sheath layer, and prepares the photovoltaic cable by melting and extruding a preheated cable core.
[0038] Specifically, the preparation method of the present invention comprises: S1, preparing a first PVC by suspension polymerization; S2, preparing a second PVC by an emulsion method; S3, using the second PVC to modify the porous PET to obtain modified PET; S4. Melt-extrude the raw materials including the first PVC and the modified PET, and coat the surface of the cable core as a sheath layer to obtain a photovoltaic cable.
[0039] The purpose of the present invention is to modify porous PET using a second PVC prepared by an emulsion method, in order to improve the compatibility between the porous PET and the first PVC, thereby improving the homogeneity, performance parameters and service life of the sheath layer.
[0040] The key factor to achieve the above purpose is to make the second PVC adhere to the surface of the porous PET evenly, effectively and in large quantities. The present invention starts from the following three aspects and ensures the above purpose through process improvement: the second PVC is ensured to have a smaller particle size and better fluidity through the emulsion method; the pores and pore diameters of the porous PET are ensured to be uniform through the emulsification method and water phase extraction; and the second PVC and the modified PET are promoted to adsorb each other through electrostatic action.
[0041] Before introducing the modification method of PET material, the present invention first introduces the manufacturing method of the first PVC as the main material of the sheath layer. The first PVC is hard PVC. In cable engineering, hard PVC sheath is widely used in power cables and communication cables. It has good electrical insulation performance, flame retardant performance and corrosion resistance.
[0042] Rigid PVC is generally prepared by suspension polymerization. The PVC obtained by the suspension polymerization process has a larger particle size (generally around 100 microns to 150 microns), a dense structure, easy processing, and high strength.
[0043] The principle of suspension polymerization is to disperse the vinyl chloride monomer containing the initiator in the medium (usually water) in the form of small droplets under the action of the suspending agent to carry out the polymerization reaction. During the reaction, each small droplet is equivalent to a small bulk polymerization unit, and the polymerization reaction is carried out in each small droplet.
[0044] The suspension polymerization process parameters used in the present invention are as follows: S11, dissolving and uniformly dispersing the dispersant in water at a mass ratio of dispersant: first initiator: water = (0.2-1): (1-3): 100, adjusting the pH value to 7 to 9, adding the first initiator dissolved in an organic solvent, and feeding into a polymerization kettle; S12, adding the first vinyl chloride monomer to the polymerization kettle at a mass ratio of the first vinyl chloride monomer: water = (200-300): 100 and according to the amount of water added in S11, to form a suspension with water; S13, in an inert gas atmosphere, heating the sealed polymerization kettle to 55° C. to 65° C. to carry out a polymerization reaction and detecting the pressure in the polymerization kettle; S14. When the real-time pressure in the polymerization kettle drops to 25% to 30% of the peak pressure in the polymerization kettle, the polymerization reaction is terminated, the temperature is lowered and the pressure is released, the solids are separated, washed and dried, and the first PVC is obtained.
[0045] The dispersant used in the present invention is specifically a mixture of polyvinyl alcohol and hydroxypropyl methylcellulose prepared in a mass ratio of 1:2. The first initiator and the second initiator used below can be the same or different. The first initiator can specifically be dibenzoyl peroxide or azobisisobutyronitrile.
[0046] The pH adjuster of S11 can be a sodium hydroxide or potassium hydroxide aqueous solution with a relatively low concentration (3wt% to 6wt%), or a weakly alkaline sodium bicarbonate aqueous solution.
[0047] The amount of the organic solvent in S11 can be selected by a person skilled in the art, and it only needs to be sufficient to dissolve the first initiator. The organic solvent in S11 can be toluene.
[0048] The purity of the first vinyl chloride monomer and the second vinyl chloride monomer below needs to be greater than 99.9%. When preparing the suspension, the first vinyl chloride monomer can be uniformly dispersed in water by stirring.
[0049] The inert gas protection atmosphere of the polymerization kettle is created by nitrogen. The polymerization kettle needs to be sealed first and nitrogen is introduced to exclude air. After heating, the pressure in the polymerization kettle can reach 0.8MPa to 1MPa during the polymerization reaction. The pressure in the polymerization kettle is monitored in real time. When the real-time pressure in the polymerization kettle drops to 25% to 30% of the peak pressure in the polymerization kettle (about 0.2MPa to 0.3MPa), it indicates that the polymerization reaction is close to completion. At this time, a terminator is added to terminate the polymerization reaction, the temperature is lowered and the pressure is released, the solids are separated, and the first PVC is obtained by washing and drying.
[0050] The terminator is specifically diethylhydroxylamine. After cooling and depressurizing, the unreacted first vinyl chloride monomer can be recovered by a condenser. The solids are separated by centrifugation, and the dispersant and the first initiator are removed by washing. The drying of the first PVC needs to ensure that its water content is less than 0.5%.
[0051] In order to ensure that the second PVC used to modify PET has a smaller particle size and better fluidity, the present invention prepares the second PVC by an emulsion method. The second PVC is a PVC paste resin, and its preparation process is as follows: S21, dissolving glutamic acid in water at a mass ratio of glutamic acid: water = (4-6): 100 to prepare a second aqueous phase; S22, according to the mass ratio of stabilizer: second initiator: plasticizer: emulsifier: second vinyl chloride monomer = (8-12): (1-2): (1-2): (2-8): 100, the stabilizer, the second initiator, the plasticizer, the emulsifier and the second vinyl chloride monomer are uniformly mixed to prepare a second oil phase; S23, adding the second aqueous phase dropwise into the second oil phase at a mass ratio of second aqueous phase: second oil phase = (100-150): 100 and emulsifying to obtain a second emulsion; S24, adding polyvinyl alcohol and water to the second emulsion, heating and stirring to react and standing, centrifuging and separating the product, washing, and obtaining a second PVC.
[0052] Among them, S21, S22 and S23 are all carried out at room temperature. The stabilizer used in S22 is octadecane. The second initiator used in S22 is azobisisobutyronitrile. The plasticizer used in S22 is dioctyl phthalate. The emulsifier used in S22 is Tween 80.
[0053] The emulsification of S23 needs to be carried out under a higher magnetic stirring speed or certain ultrasonic conditions. Specifically, if magnetic stirring is used, the stirring speed needs to be at least 4000rpm / min to 5000rpm / min. If ultrasonic emulsification is used, the ultrasonic power needs to be at least 400W to 600W, and the ultrasonic frequency needs to be at least 1400Hz. Regardless of magnetic stirring or ultrasonic treatment, the treatment time can be selected by those skilled in the art as long as sufficient emulsification is achieved.
[0054] By dropping the second aqueous phase into the second oil phase, water-in-oil droplets are obtained. In order to achieve aqueous phase extraction using hydrophilic polyvinyl alcohol, in S24, the mass of the added polyvinyl alcohol is 6% to 8% of the mass of the water added in S21. In S24, the mass of the added water is 200% to 250% of the mass of the water added in S21. In S24, the method of adding polyvinyl alcohol and water is: polyvinyl alcohol and one-third of water are added to the second emulsion and mixed evenly, heated together to 95°C to 98°C, and then the remaining two-thirds of water are added, and the reaction is stirred at a temperature of 95°C to 98°C for 2h to 4h. The reaction is carried out under low-speed stirring of 100rpm / min to 200rpm / min. After the heating and stirring reaction is completed, the standing time is 20min to 40min. After washing, the S24 product is preferably dried. The drying temperature does not exceed 100°C.
[0055] In order to ensure that the pores and pore sizes of the porous PET are uniform, the porous PET of the present invention is prepared by the following steps: A1. Using acetylated chitosan as a porogen and inorganic non-metallic oxide as a flame retardant, adding acetic acid and water and mixing evenly to prepare a suspended first aqueous phase; A2, using PET and organic solvent to prepare the first oil phase; A3, obtaining a first emulsion by mixing and emulsifying the first water phase and the first oil phase; A4. Add polyvinyl alcohol to the first emulsion, heat and stir evenly, let it stand, and then distill under reduced pressure to remove the solvent to obtain porous PET.
[0056] Specifically, in step A1, the mass ratio of acetylated chitosan: inorganic non-metallic oxide: acetic acid: water is (1-2): (2-4): (4-8): 100. The acetic acid used in A1 is 100% pure acetic acid.
[0057] In order to prevent the degradation of PET caused by dehydration of common chitosan containing hydroxyl groups in the melting process, the present invention prepares acetylated chitosan by the following method: B1. Disperse chitosan evenly in acetic acid and heat to 45°C to 65°C, add concentrated sulfuric acid and stir, keep warm for 20 to 30 minutes after stirring, then add acetic anhydride and stir and keep warm for 1.5 to 2.5 hours; B2. Evaporating the acetic acid under reduced pressure, washing the solids, and drying them to obtain acetylated chitosan.
[0058] In B1, by mass ratio, concentrated sulfuric acid: acetic anhydride: chitosan: acetic acid = (2-3): (4-5): (8-12): 100. The concentration of concentrated sulfuric acid is 98%. The acetic acid is pure acetic acid with a concentration of 100%.
[0059] The purpose of adding concentrated sulfuric acid and stirring is to activate the hydroxyl groups of chitosan with the concentrated sulfuric acid, and then form an ester bond between the hydroxyl groups of chitosan and the acyl groups of acetic anhydride through an esterification reaction to obtain acetylated chitosan.
[0060] In order to improve the flame retardant properties of porous PET, a flame retardant is also added when preparing the first aqueous phase. The advantage of using inorganic non-metallic oxides as flame retardants is that they are environmentally friendly and pollution-free, and they are helpful in improving the mechanical properties of the sheath layer. The inorganic non-metallic oxides can be selected from materials such as aluminum oxide, magnesium oxide, and antimony oxide. Considering that flame retardants such as aluminum hydroxide and magnesium hydroxide will release interlayer free water at high temperatures, causing PET to degrade, the present invention does not use hydroxide flame retardants to treat porous PET. Preferably, the inorganic non-metallic oxide of the present invention selects magnesium oxide.
[0061] In step A2, the mass ratio of PET to organic solvent is (6-12): 100, and the organic solvent includes phenol and tetrachloroethane in a mass ratio of 1:1. In step A2, the first oil phase is prepared by heating PET and the organic solvent to 65° C. to 75° C., keeping the temperature, and magnetically stirring at a speed of 400 rpm / min to 500 rpm / min until the PET is completely dissolved.
[0062] In step A3, the mass ratio is (80-120): 100 for the first water phase and the first oil phase. In step A3, the mixing and emulsification is performed by dropping the first water phase into the first oil phase at 65° C. to 75° C. and stirring, and after the dropping is completed, the first water phase is kept warm and ultrasonically emulsified at a power of 400 W to 600 W and a frequency of 60 kHz to 80 kHz for 20 min to 40 min.
[0063] In step A4, the mass ratio of the first emulsion to polyvinyl alcohol is 100: (6-12). In step A4, the heating and stirring are performed uniformly by magnetically stirring at a temperature of 95° C. to 98° C. at a speed of 100 rpm / min to 200 rpm / min until the polyvinyl alcohol is completely dissolved. In step A4, the mixture is cooled naturally during the standing process, and the standing time is 20 min to 40 min. In step A4, after the reduced pressure distillation, the solids are extracted, washed and dried to obtain porous PET.
[0064] In order to promote mutual adsorption between the second PVC and the modified PET, step S3 specifically includes: S31, mixing the second PVC in tetrahydrofuran in a mass ratio of second PVC: porous PET: water: tetrahydrofuran = (4-6): (20-25): (8-12): 100, adding the mixture of porous PET and water, adjusting the pH value to 7 to 8, and performing ultrasonic treatment; S32. After the ultrasonic treatment is completed, tetrahydrofuran and water are removed by rotary evaporation to obtain modified PET.
[0065] The ultrasonic treatment conditions are 200W to 400W power and 800Hz to 1000Hz frequency for 15min to 30min. The pH value is adjusted to 7 to 8 to ensure a neutral or weakly alkaline environment to achieve mutual adsorption between the second PVC and the porous PET based on electrostatic action.
[0066] After obtaining the first PVC and modified PET, a sheath layer can be formed on the surface of the cable core by melt extrusion. Step S4 specifically includes: S41, laying out the cable core and preheating it; S42. According to the mass ratio of auxiliary agent: modified PET: first PVC = (4-8): (10-15): 100, the raw materials including auxiliary agent, modified PET and first PVC are melt-extruded at a temperature of 180°C to 200°C, coated on the surface of the cable core, and then wound up after cooling to obtain a photovoltaic cable.
[0067] The preheating temperature of S41 does not exceed 160°C. The additives of S42 can be selected and added by those skilled in the art. The additives mainly include antioxidants, plasticizers, lubricants, stabilizers, inorganic fillers, etc. The selection of the above additives belongs to the prior art, and the present invention will not be repeated here. Melt extrusion is carried out using a melting device and a screw extrusion device, and the temperature range of the melting device and the speed of the screw extrusion device can be selected and adjusted by those skilled in the art. The melting time is preferably 20 minutes to 40 minutes.
[0068] Specific examples are given below. The water used in the following specific examples is deionized water, and the acetic acid is 100% pure acetic acid.
[0069] Embodiment 1 This example prepares an acetylated chitosan, and its preparation process is as follows: Chitosan was dispersed and stirred in acetic acid at a mass ratio of concentrated sulfuric acid: acetic anhydride: chitosan: acetic acid = 2:4:10:100 until completely dissolved. After heating to 50°C, 98% concentrated sulfuric acid was gradually added dropwise and slowly stirred with a stirring rod. After the addition and stirring were completed, the temperature was kept for 20 minutes. Then, acetic anhydride was gradually added dropwise and slowly stirred with a stirring rod. After the addition was completed, magnetic stirring was turned on, stirred at a speed of 180 rpm / min, and the temperature was kept at 50°C for 2 hours. After the reaction was completed, acetic acid was evaporated under reduced pressure, and the solid was washed with ethanol and water, and infrared drying was performed below 80°C to obtain acetylated chitosan.
[0070] Embodiment 2 In this embodiment, a PVC material is prepared, which is used as the first PVC in subsequent embodiments. The preparation process is as follows: 1. Dissolve polyvinyl alcohol and hydroxypropyl methylcellulose in water and disperse them evenly according to the mass ratio of polyvinyl alcohol: hydroxypropyl methylcellulose: azobisisobutyronitrile: water = 0.3:0.6:2:100, add sodium bicarbonate aqueous solution to adjust the pH value to 8, add toluene dissolved in toluene, and feed into the polymerization kettle; 2. According to the mass ratio of the first vinyl chloride monomer to water = 250:100, according to the amount of water added in the above steps, add the first vinyl chloride monomer to the polymerization kettle and stir to form a suspension with water; 3. The polymerization kettle was sealed, nitrogen was introduced to exclude air, the polymerization kettle was heated to 60° C., the temperature was kept and the pressure in the polymerization kettle was monitored in real time. In view of the peak pressure in the polymerization kettle being 0.86 MPa, when the pressure in the polymerization kettle dropped to 0.25 MPa, diethylhydroxylamine was added to terminate the polymerization reaction, the temperature was lowered and the pressure was released, the unreacted first vinyl chloride monomer was recovered, the solid was separated by centrifugation, the solid was washed with ethanol and water, and infrared drying was performed below 80° C. to obtain the first PVC.
[0071] Embodiment 3 In this embodiment, a PVC material is prepared, which is used as the second PVC in subsequent embodiments. The preparation process is as follows: 1. Prepare the second aqueous phase by stirring glutamic acid in water at room temperature until it is completely dissolved according to the mass ratio of glutamic acid to water = 5:100; 2. According to the mass ratio of octadecane:azobisisobutyronitrile:dioctyl phthalate:Tween 80:second vinyl chloride monomer =(8-12):(1-2):(1-2):(2-8):100, octadecane, azobisisobutyronitrile, dioctyl phthalate, Tween 80 and the second vinyl chloride monomer are uniformly mixed to prepare the second oil phase; 3. According to the mass ratio of the second water phase to the second oil phase = 150:100, the second water phase is added dropwise into the second oil phase and stirred with a stirring rod simultaneously. After the addition is completed, ultrasonic emulsification is performed at a power of 500 W and a frequency of 1600 Hz for 20 minutes to obtain a second emulsion; 4. Weigh 6% of the mass of polyvinyl alcohol and twice the mass of water in step 1, add all the polyvinyl alcohol and one-third of the water weighed in this step to the second emulsion and mix evenly, heat them together to 96°C, add the remaining two-thirds of the water, heat to 96°C again, stir at a low speed of 100 rpm / min, react for 2h, and after the reaction is completed, let it stand for 20min, wash the product with ethanol and water, and infrared dry below 80°C to obtain a second PVC sample 1.
[0072] Embodiment 4 This embodiment prepares a PVC material, which is used as the second PVC in subsequent embodiments. The difference between this embodiment and the second PVC sample 1 prepared in embodiment 3 is that glutamic acid is replaced by sodium chloride. The other preparation processes are the same as those in embodiment 3. The second PVC sample 2 is prepared in this embodiment.
[0073] Embodiment 5 In this embodiment, a series of modified porous PET samples 1 to 4 were prepared. The raw material selection and proportions are listed in Table 1. The preparation process is as follows: 1. Mix chitosan, flame retardant, acetic acid and water, and stir at room temperature until chitosan is completely dissolved to prepare a suspended first aqueous phase; 2. Mix PET, phenol and tetrachloroethane, heat to 65°C, keep warm and stir magnetically at 400 rpm / min until PET is completely dissolved to prepare the first oil phase; 3. According to the mass ratio of the first water phase to the first oil phase = 100:100, the first water phase is added dropwise into the first oil phase at 70°C and stirred simultaneously. After the addition is completed, the mixture is kept warm and ultrasonically emulsified at a power of 500 W and a frequency of 80 kHz for 20 minutes to obtain a first emulsion; 4. Add polyvinyl alcohol to the first emulsion, heat to 96°C, and stir magnetically at 100 rpm / min until the polyvinyl alcohol is completely dissolved. Let stand for 30 minutes and cool naturally, remove the solvent by vacuum distillation, extract the solid, wash the solid with ethanol and water, and dry it with infrared at below 80°C to obtain porous PET; 5. The second PVC sample 1 obtained in Example 3 was uniformly mixed in tetrahydrofuran at a mass ratio of second PVC: porous PET: water: tetrahydrofuran = 4:25:10:100, a mixture of porous PET and water was added, the pH value was adjusted to 8, and ultrasonic treatment was performed at a power of 200 W and a frequency of 800 Hz for 15 min; 6. After the ultrasonic treatment, tetrahydrofuran and water were rotary evaporated to obtain modified porous PET samples 1 to 4.
[0074] Table 1 In this embodiment, porous PET sample 5 is prepared, and its raw material selection, raw material ratio, and preparation process are basically the same as those of porous PET sample 3. The only difference is that the second PVC used is the second PVC sample 2 obtained in Example 4.
[0075] Embodiment 7 In this embodiment, porous PET sample 6 is prepared. The raw material selection, raw material ratio and preparation process are basically the same as those of porous PET sample 3. The only difference is that the flame retardant used is magnesium hydroxide.
[0076] Embodiment 8 In this embodiment, porous PET sample 7 is prepared, and its raw material selection, raw material ratio, and preparation process are basically the same as those of porous PET sample 3. The only difference is that the magnesium oxide flame retardant is replaced by silicon dioxide.
[0077] Embodiment 9 This embodiment prepares sheath samples 1 to 7 that can be used as sheath layer materials. The difference between sheath samples 1 to 7 is that porous PET samples 1 to 7 are used in sequence. The preparation method of sheath samples 1 to 7 is as follows: According to the mass ratio of diisodecyl phthalate: calcium zinc dimerate: pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]: glyceryl monostearate: porous PET: first PVC = 1:1:1:1:15:100, the above raw materials are melt-extruded at a temperature of 180°C to 200°C to obtain a sheath sample. The first PVC is prepared by Example 2.
[0078] It can be understood that if the extruded material is coated on the surface of the cable core in the above steps, a photovoltaic cable can be obtained. In order to test the performance of the sheath material in this embodiment, it is directly extruded and then cooled to form.
[0079] Performance Testing The present invention uses a laser diffraction particle size analyzer (Mastersizer 3000) to test the particle size of PVC. The average particle sizes (obtained by calculating the weighted average diameter of the particle volume) of the samples obtained in Example 2, Example 3 and Example 4 are 183 microns, 23 microns and 25 microns, respectively.
[0080] The present invention tests the performance of sheath samples 1 to 7. The testing standards for tensile strength and elongation at break refer to GB / T1701-2001, and the testing standard for limiting oxygen index refers to GB / T2406.12008. In order to measure the anti-aging effect of the samples, the aging test conditions (temperature 80°C, time 144h) refer to the aging conditions of the non-electrical test of polyvinyl chloride sheath in GB / T5023.
[0081] The flame retardant test results of the sheath samples 1 to 7 are shown in Table 2. The test results show that the samples 1 to 6 with the addition of flame retardants all exhibited acceptable flame retardant properties. Among them, the flame retardant property of sample 6 with the addition of magnesium hydroxide flame retardant was the best. Sample 7 with the addition of silicon oxide performed poorly in terms of flame retardant properties.
[0082] Table 2 The tensile strength and elongation at break test results of sheath samples 1 to 7 are shown in Table 3. In terms of tensile strength and elongation at break, samples 1, 2, 3, 4, 6 and 7 all performed well. Sample 5 performed poorly, which may be due to the poor bonding and compatibility between porous PET sample 5 and the first PVC sample of Example 2. After aging treatment, samples 3, 4, 6 and 7 all performed well. The change rates of samples 1 and 2 were high, which may be due to the fact that chitosan has not been acetylated.
[0083] Table 3 Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A method for preparing a green, environmentally friendly, heat-resistant photovoltaic cable, characterized in that: include: S1, preparing a first PVC by suspension polymerization; S2, preparing a second PVC by an emulsion method; S3, using the second PVC to modify the porous PET to obtain modified PET; S4. Melt-extrude the raw materials including the first PVC and the modified PET, and coat them on the surface of the cable core as a sheath layer to obtain the photovoltaic cable.
2. The preparation method according to claim 1, characterized in that: The first PVC is hard PVC, and the second PVC is PVC paste resin.
3. The preparation method according to claim 1, characterized in that: The porous PET is prepared by the following steps: A1. Using acetylated chitosan as a porogen and inorganic non-metallic oxide as a flame retardant, adding acetic acid and water and mixing evenly to prepare a suspended first aqueous phase; A2, using PET and organic solvent to prepare the first oil phase; A3, obtaining a first emulsion by mixing and emulsifying the first aqueous phase and the first oil phase; A4. Add polyvinyl alcohol to the first emulsion, heat and stir evenly, let stand, and then distill under reduced pressure to remove the solvent to obtain the porous PET.
4. The preparation method according to claim 3, characterized in that: In step S2, the raw materials used include glutamic acid.
5. The preparation method according to claim 3, characterized in that: In step A1, the mass ratio of acetylated chitosan: inorganic non-metallic oxide: acetic acid: water is (1-2): (2-4): (4-8): 100; and / or In step A2, the mass ratio of PET: organic solvent = (6-12): 100; and / or In step A2, the organic solvent comprises phenol and tetrachloroethane in a mass ratio of 1:1; and / or In step A2, the first oil phase is prepared by heating the PET and the organic solvent to 65° C. to 75° C., maintaining the temperature and magnetically stirring at a speed of 400 rpm / min to 500 rpm / min until the PET is completely dissolved; and / or In step A3, the mass ratio of the first aqueous phase to the first oil phase is (80-120): 100; and / or In step A3, the mixing and emulsification is carried out by dropping the first aqueous phase into the first oil phase at 65° C. to 75° C. and stirring, and after the dropping is completed, keeping the temperature and ultrasonically emulsifying at a power of 400 W to 600 W and a frequency of 60 kHz to 80 kHz for 20 min to 40 min; and / or In step A4, the mass ratio of the first emulsion to polyvinyl alcohol is 100: (6-12); and / or In step A4, the heating and stirring are performed uniformly by: magnetically stirring at a temperature of 95° C. to 98° C. and a speed of 100 rpm / min to 200 rpm / min until the polyvinyl alcohol is completely dissolved; and / or In step A4, the step of cooling the device naturally during the standing process is performed, and the standing time is 20 to 40 minutes; and / or In step A4, after the reduced pressure distillation, the solid matter is extracted, washed and dried to obtain the porous PET.
6. The preparation method according to any one of claims 1 to 5, characterized in that Step S1 specifically includes: S11, dissolving and uniformly dispersing the dispersant in the water at a mass ratio of dispersant: first initiator: water = (0.2-1): (1-3): 100, adjusting the pH value to 7 to 9, adding the first initiator dissolved in an organic solvent, and feeding into a polymerization kettle; S12, adding the first vinyl chloride monomer to the polymerization kettle at a mass ratio of the first vinyl chloride monomer: water = (200-300): 100 and according to the amount of water added in S11 to form a suspension with the water; S13, in an inert gas atmosphere, heating the sealed polymerization kettle to 55° C. to 65° C. to carry out a polymerization reaction and detecting the pressure in the polymerization kettle; S14. When the real-time pressure in the polymerization kettle drops to 25% to 30% of the peak pressure in the polymerization kettle, the polymerization reaction is terminated, the temperature is reduced and the pressure is released, the solid is separated, and the solid is washed and dried to obtain the first PVC.
7. The preparation method according to any one of claims 1 to 5, characterized in that Step S2 specifically includes: S21, dissolving the glutamic acid in the water at a mass ratio of glutamic acid: water = (4-6): 100 to prepare a second aqueous phase; S22, mixing the stabilizer, the second initiator, the plasticizer, the emulsifier and the second vinyl chloride monomer uniformly according to a mass ratio of stabilizer: second initiator: plasticizer: emulsifier: second vinyl chloride monomer = (8-12): (1-2): (1-2): (2-8): 100 to prepare a second oil phase; S23, adding the second aqueous phase dropwise into the second oil phase and emulsifying the second oil phase at a mass ratio of second aqueous phase: second oil phase = (100-150): 100 to obtain a second emulsion; S24, adding polyvinyl alcohol and water to the second emulsion, heating and stirring to react and standing, centrifuging and separating the product, washing, and obtaining the second PVC.
8. The preparation method according to any one of claims 1 to 5, characterized in that Step S3 specifically includes: S31, mixing the second PVC in the tetrahydrofuran in a mass ratio of second PVC: porous PET: water: tetrahydrofuran = (4-6): (20-25): (8-12): 100, adding the mixture of the porous PET and the water, adjusting the pH value to 7 to 8, and performing ultrasonic treatment; S32, after the ultrasonic treatment is completed, the tetrahydrofuran and the water are removed by rotary evaporation to obtain the modified PET.
9. The preparation method according to any one of claims 1 to 5, characterized in that: Step S4 specifically includes: S41, laying out and preheating the cable core; S42. According to the mass ratio of auxiliary agent: modified PET: first PVC = (4-8): (10-15): 100, the raw materials including the auxiliary agent, the modified PET and the first PVC are melt-extruded at a temperature of 180° C. to 200° C., coated on the surface of the cable core, and then wound up after cooling to obtain the photovoltaic cable.
10. A green, environmentally friendly, heat-resistant photovoltaic cable, characterized in that: The green, environmentally friendly, heat-resistant photovoltaic cable is obtained by the preparation method as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Impact modified polyvinyl chloride cable material
CN104861352A
Formula of insulating cable jacket encapsulation
CN105348575A
Low temperature impact resistant modified polyvinyl chloride cable material
CN107090147A
PET-based polymer matrix for electrical wires
CN114729176A
Mineral insulation isolation type fireproof cable
CN117766215A